Pengembangan Sistem Informasi Manajemen dan Pengawasan Dokumen Akta berbasis Web (Studi Kasus: Kantor Notaris dan PPAT Ade Suryatini S.H., M.Kn.) - Adha Apriliosusworo; Djoko Purnomo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Notary Office and PPAT Ade Suryatini is a notary office located in Grogol, Jakarta, which every day makes many deed documents based on requests from clients. Based on an interview with Ms. Ade Suryatini as a notary, there are two problems in the deed-making process, namely the difficulty of employees in finding deed documents that are being worked on or those that have been completed and the process of monitoring the deed document processing is still done manually. Therefore, a management information system and supervision of deed documents was made which can be a solution for both problems. System development is carried out using the waterfall model SDLC method with web-based implementation. At the requirements analysis stage, user requirements and functional requirements of the system are obtained which produce use cases. Then do the system design which includes sequence diagrams, class diagrams, database design and interface design. From database design and interface design, database implementation is carried out using mysql and interface design using the laravel framework. Then the last stage is testing the system that has been implemented using validation testing using blackbox testing which produces 38 test cases with 100% valid results and user acceptance testing testing which produces a final value of 99%.